A La Niña‐Like Climate Response to South African Biomass Burning Aerosol in CESM Simulations. Issue 6 (12th March 2020) - Amiri‐Farahani, Anahita; Allen, Robert J.; Li, King‐Fai; Nabat, Pierre; Westervelt, Daniel M.
Abstract: The climate response to atmospheric aerosols, including their effects on dominant modes of climate variability like El Niño–Southern Oscillation (ENSO), remains highly uncertain. This is due to several sources of uncertainty, including aerosol emission, transport, removal, vertical distribution, and radiative properties. Here, we conduct coupled ocean‐atmosphere simulations with two versions of the Community Earth System Model (CESM) driven by semiempirical fine‐mode aerosol direct radiative effects without dust and sea salt. Aerosol atmospheric heating off the west coast of Africa—most of which is due to biomass burning—leads to a significant atmospheric dynamical response, including localized ascent and upper‐level divergence. Coupled Model Intercomparison Project version 6 (CMIP6) biomass burning simulations support this response. Moreover, CESM shows that the anomalous aerosol heating in the Atlantic triggers an atmospheric teleconnection to the tropical Pacific, including strengthening of the Walker circulation. The easterly trade winds accelerate, and through coupled ocean‐atmosphere processes and the Bjerknes feedback, a La Niña‐like response develops. Observations also support a relationship between south African biomass burning emissions and ENSO, with La Niña events preceding strong south African biomass burning in boreal fall. Our simulations suggest a possible two‐way feedback between ENSO and south African biomass burning, with La Niña promoting more biomass burning emissions, which may then strengthen the developing La Niña. Key Points: South African biomass burning aerosol locally warms the atmosphere This heating drives local ascent and divergence, triggering a teleconnection to the Pacific The Pacific Walker circulation strengthens, and a La Niña‐like response develops